The prevalence of the metabolic syndrome in a farm worker community in the Boland district, South Africa - Maritza J. Kruger; Theo A. Nell (BMC, 2017)
Abstract Background In South Africa, not much is known about MetS in farm working communities. This study aimed to describe the prevalence of the MetS in a farm working population from the Boland winelands district of the Western Cape, South Africa. Methods A cross-sectional study was followed among farm workers (aged 20-60 years) from surrounding wine estates. The questionnaires used described socio-demographic status, ethnic background, alcohol consumption, smoking, exercise and daily medication. Anthropometric assessments were performed and blood pressure measurements taken prior to blood sampling for serum insulin, glucose and fasting lipogram profiles. Results The prevalence of the MetS was higher in women (46.3 vs 29.3%). Both men and women in the MetS group had a significantly higher waist circumferences (WC; p < 0.001 for both), whilst higher glucose levels were only significantly higher in the women (p < 0.001). Correlations showed significant differences between body mass index (BMI), WC and waist to hip ratio (W:H) and the different MetS risk factors. Conclusions The female population in this study showed higher prevalence rates for the individual risk factors and the MetS overall. There is an urgent need to develop culturally sensitive health promotion programs addressing risk factors for metabolic syndrome among farm workers.